Evaluation of the magnetic phase in stainless steel AISI 304 worked in cold and its recovery by heat treatment - Dionicio Padilla, Eusebio (2006)
The Project of Investigation called: Evaluation of the magnetic phase in Stainless steel AISI 304, worked in cold and its recovery by Heat Treatment has determined that the material of testing submitted to loads by compression is magnetized, which increasing its hardness and transforming partially the austenitic structure in martensitic. The material of transformed structure was submitted to heat treatment to 700 oC and 800 oC respectively which origins the recovery of the structure.